Unpuddled transplanting: a productive, profitable and energy efficient establishment technique in rice under Eastern sub-Himalayan plains - Mitra, Biplab; Patra, Koushik; Bhattacharya, P M; Chowdhury, A K (ORYZA-An International Journal of Rice, 2018)
The study was undertaken in sandy loam soils of Eastern sub-Himalayan plains with the objectives to arrive at optimal tillage requirement in rice to economise on fuel, labour, time and energy & also to judge the performances of different promising varieties of this zone under those alternative crop establishment techniques for getting higher profitability. The experiment was laid out in a split-plot design having 20 treatment combinations in 3 replicates. Four different crop establishment methods viz., direct seeding through zero till drill (DSR), bed planting (BP), unpuddled transplanting (UPTR) and puddled transplanting(PTR) in main plot and five different varieties viz., Swarna sub 1, Pratiksha, IET 5656, Naveen and MTU 7029 in sub plots were allocated randomly. It was revealed that PTR recorded significantly higher grain yield (4502 kg ha-1) in the first year, while UPTR recorded maximum grain yield (4616 kg ha-1) during second year of experimentation, being at par with PTR (4606 kg ha-1). Grain yield varied significantly among the varieties in both the years of experimentation. Swarna Sub 1 (3779 kg ha-1) in first year and Pratiksha (4215 kg ha-1) in second year recorded maximum grain yield. Use of machineries under alternate cop establishment techniques reduced the fuel, labour and time requirement under those alternate crop establishment techniques. The total energy input in rice were reduced to 9269.95, 7865.00 and 7589.30 MJ ha-1 under UPTR, BP and DSR, respectively, due to less fuel and labour requirement as compared to PTR(10862.30 MJ ha-1). It was interesting to note that despite higher output energy and net energy gain under PTR, energy efficiency was recorded maximum under UPTR (15.88) reflecting its higher efficiency over other crop establishment techniques. Despite higher gross returns under PTR, UPTR reflected a higher net return in both the years of experimentation. As the yields were similar in PTR and UPTR, reduced cost of cultivation under UPTR resulted in much higher net returns for all the varieties.Â It can be concluded that unpuddled transplanting in rice would be the most viable option in rice-wheat cropping system in Eastern sub-Himalayan plains in terms of productivity, energy-efficiency as well as profitability.